Aluminium phosphide induced pancreatitis - Nadeem, Mir; Phogat, Vishal; Waseem, Mir; Shah, Tabinda Ayub (International Journal of Research in Medical Sciences, 2019)
Aluminium Phosphide (AlP) is a commonly used agricultural pesticide. It is cheap, effective, and easily available. Aluminium Phosphide is used as a rodenticide, insecticide, and fumigant to preserve stored cereal grains, also known as "Wheat pills". In Iran, it is known as the rice tablet. There, have been frequent incidents of accidental or intentional deaths. There have been only a few case reports on aluminum phosphide-induced pancreatitis in the literature available. In this report, we present the case of a young man who developed acute pancreatitis following ingestion of aluminum phosphide pellet in the absence of the usual risk factors and after exclusion of other possible causes of pancreatitis. 35-year-old male came to the ER of SGT Hospital, Gurugram, one hour after ingestion of a single 3 g tablet of Aluminium Phosphide (Celphos) at home, with a suicidal intent. He had three episodes of Vomiting on the way to the hospital. On Day 1 of admission, USG abdomen showed heterogeneity of head and the body of pancreas with minimal peri-pancreatic fluid, suggestive of Pancreatitis. Serum Amylase and lipase levels were raised throughout the hospital course. CT images were suggestive of pancreatitis. The signs and symptoms of Acute AlP Poisoning are non-specific, dose dependent and evolve with time. After ingestion, toxic features usually develop within a few minutes. The major lethal consequence of AlP ingestion is profound circulatory collapse, secondary to direct effects of toxins on cardiomyocytes, fluid loss, and adrenal gland damage. Our patient was diagnosed with acute pancreatitis in first 24hours of admission with high suspicion of pancreatitis and managed well with iv fluids and supportive treatment and was discharged after 3 weeks of in hospital stay.